Urinary and anal dysfunction after laparoscopic versus laparotomic radical hysterectomy. (November 2015) - Laterza, Rosa M.; Salvatore, Stefano; Ghezzi, Fabio; Serati, Maurizio; Umek, Wolfgang; Koelbl, Heinz
Abstract: Objective: The aim of this study was to compare urinary and anal dysfunction after laparoscopic (LRH) and abdominal (ARH) radical hysterectomy for cervical cancer. Study design: Consecutive patients who underwent radical hysterectomy for treatment of cervical cancer were enrolled in this study and divided into two groups, according to the surgical approach. Urinary and anal symptoms were evaluated before and 6 months after surgery. Results: Fifty-four women were considered: 27 LRH and 27 ARH. Urinary incontinence was significantly more frequent both after LRH (37% vs 86.9%, p = 0.0004) and after ARH (33.3% vs 100%, p < 0.0001); urge incontinence (3.7% vs 29.6%, p = 0.02) and increased bladder sensation (0 vs 22.2%, p = 0.02) were significantly more common postoperatively in patients undergone ARH. In both groups more patients complain about increase of straining during voiding (LRH: 0 vs 34.7%, p = 0.009; ARH: 3.7% vs 29.6% p = 0.02) after surgery. Postoperative constipation by obstructed defecation was more frequent after ARH (Wexner score: 0 vs 2, p = 0.03) but not after LRH. Conclusion: From our results, laparoscopic approach for radical hysterectomy seems to reduce the postoperative occurrence of urge incontinence, increased bladder sensation and constipation by obstructed defecation, in comparison with abdominal radical surgery.